Transplantation of the Bowman’s layer in cases of biomechanical instability of the cornea after radial keratotomy - O. G. Oganesyan; P. M. Ashikova; A. V. Ivanova; K. B. Letnikova; C. O. Oganesyan; P. V. Makarov (Российский офтальмологический журнал)
Late complications of radial keratotomy (RK), are as a rule caused by a change in the biomechanical properties of the cornea.Purpose: to study the long-term stabilizing effect of the Bowman’s layer (BL) transplantation after RK.Material and methods. In a limited, prospective, monocentric pilot study we operated 2 male patients (2 eyes) aged 60 and 55. The radial incisions had been performed 34 and 38 years ago. The indications for surgery were progressive biomechanical instability of the cornea and functional refractive visual fluctuations. Within 12 months after the operation, complications, corrected visual acuity, keratometric parameters, biomicroscopic transparency of the cornea, and patient satisfaction were assessed.Results. No complications were noted during the follow-up period, the cornea and graft retained transparency. The average thickness of the BS graft was 20±2.1 µm. The average visual acuity corrected by contact lenses increased from 0.4±0.3 to 0.65±0.1, the average indicator of keratometric astigmatism changed from 1.9±1.6 to 3.0 D, these indicators remained after 6, 9 and 12 months, which indicates that biomechanical stability of the cornea was achieved and that the refractive-visual fluctuations are absent.Conclusion. In late term RK complications, BS transplantation partially restores the normal anatomy of the anterior surface of the cornea and ensures its biomechanical stability during a 12-month follow-up period. For the conclusions to be maximally objective, more clinical cases should be studied within a longer observation period.